(untitled) (Revista Inclusiones, 2020)
The article examines the features of protecting personal data of users of electronic services of public services. Currently, society faces problems of information security of public services, the solution of which depends on improving the current legislation and technology for providing services. The purpose of this paper is to analyze the problems of ensuring the security of personal data of users of electronic public services. The role of electronic services of public services in the development of society has been noted. Data describing the distribution of electronic public services in the countries of the world have been presented. Such an important sphere of application of information and communication technologies in Russia as e-government has been highlightedж the range of tasks assigned to it, as well as the advantages and possible problems in its use have been described.